Penentuan Kelayakan Kandang Sapi Menggunakan Metode AHP-TOPSIS (Studi Kasus: UPT Pembibitan Ternak dan Hijauan Makanan Ternak Singosari) - Edi Siswanto; Nurul Hidayat; Nurudin Santoso (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Cowshed is provided to shelter cows from the unfavorable weather and confine the cows' mobility in such a way that the fattening process gives rise to the accelerated increase of the bodyweight. Besides, cowshed of decent quality which is clean and comfortable can prevent cows from disease organisms to achieve the maximum rearing result. The problems confronted UPT-PT and HMT in Singosari in determining the decency of cowshed comprise the time efficiency and the difficulty in determining the criteria parameter used to assess the decency of the cowshed. The solution thereto is to capitalize on an intelligent system which, on the basis of the data supplied by UPT-PT and HMT in Singosari, provides a recommended measure of determining decency. The system is created in web-based using Analytical Hierarchy Process (AHP) method and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method. The AHP method was employed to gain the weight value of each criterion to be used in stage of weighting which yielded the preference value for each alternative in the TOPSIS method. The system output is an alternative data ranking based on its preference value. Testing was conducted by altering the pairwise comparison matrix in terms of the system prior to the matching between the system output and the actual data to get the level of system accuracy. The level of accuracy of the system obtained is 84.8%.